Effects of Discharge Training and Counseling Service on Self-Efficacy, Care Behaviors and the Problems Experienced in Patients Who Have Undergone Coronary Artery By-Pass Grafting Surgery: An Experimental Study - Karaöz, Süreyya; Işık, Sevcan Avcı (My University, 2022)
T Objective: The aim of this experimental study was to examine the effects of discharge training and counseling services on self-efficacy, care be- haviors, and problems experienced by patients who have undergone coronary artery bypass grafting. Material and Methods: The study was conducted with 100 patients (50 control, 50 experimental group), hospitalized in the adult car- diovascular surgery in a university hospital. Apart from the routine nursing care given to the control group, the patients in the experimental group were given dis- charge training and telephone counseling services. The patients in both groups were monitored twice after discharge: first and fourth weeks. In the study, Bar- nason Efficacy Expectation Scale (BEES) cardiac surgery version, forms of self- care behaviors, experienced problems, and telephone counseling were used. Results: At the end of the first and fourth weeks after discharge, it was found that the experimental group had more self-care behaviors (salt usage in meals p=0.001, exercising/walking p=0.001, performing activities that required physi- cal movement p=0.002, and walking at least 2 to 3 days a week for 25 minutes p=0.001), the control group had more problems, and fewer patients being able to solve the problems experienced (p<0.05). At the end of the first and fourth weeks of BEES, total and subscale mean scores were found to be higher in the experi- mental group than in the control group (p<0.05). Conclusion: The study find- ings indicate that discharge training and counseling services positively affect patients’ care behaviors, decrease the problems experienced after discharge, and increase self-efficacy.